Pemikiran Pendidikan Islam Perspektif Progresivisme-Esensialisme Plus - Tiam, Sunardji Dahri (Universitas Islam Raden Rahmat Malang, 2024)
Human opinion, practical attitude, emotion, and egoism have dominant affects upon the actualization of a basic concept. To anticipats the probable changes or deviation one needs to contemplate or review the basic concept and content of Islamic educaton from the most esensial point of view, i.e. ontological, epistimologi and axiological point of view. By epplying a descriptive-comparative method, critical historical analisis, and reflective-inductive-deductive thinking, we will be able to discover a new ontological, epistimologi and axiological synthesis and view about Islamic education that can bring us to the understanding of the philosophy of Islam.